1943
DOI: 10.1037/h0061322
|View full text |Cite
|
Sign up to set email alerts
|

The McGill Adult Comprehension Examination: "Verbal Situation" and "Picture Anomaly" Series.

Abstract: This report describes two tests, verbal and nonverbal, meant for use with adults as a supplement to the more abstract problems of existing tests (Hebb and Morton 2 ). Both "Verbal Situation Series" and "Picture Anomaly Series" concern an understanding of human behavior, and are intended to provide problems of intrinsic adult interest; together they comprise the "McGill Adult Comprehension Examination," but they need not necessarily be used together as a single test. Both are culture-loaded; norms are given for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1944
1944
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…In this presentation, Hebb stated that there was a need for new tests to “cover a wide range of adult interests” and he referred to two new tests that he was developing, the verbal test of Adult Comprehension of attitudes, motivation, etc., and a non-verbal Picture Anomaly test (described by Hebb and Morton, 1943). Cattell's presentation at the 1940 APA Meeting was a factor analysis of the concept of socioeconomic (social) status (Cattell, 1940b).…”
Section: Hebb's Dissatisfaction With the Use Of Intelligence Tests Fomentioning
confidence: 99%
See 2 more Smart Citations
“…In this presentation, Hebb stated that there was a need for new tests to “cover a wide range of adult interests” and he referred to two new tests that he was developing, the verbal test of Adult Comprehension of attitudes, motivation, etc., and a non-verbal Picture Anomaly test (described by Hebb and Morton, 1943). Cattell's presentation at the 1940 APA Meeting was a factor analysis of the concept of socioeconomic (social) status (Cattell, 1940b).…”
Section: Hebb's Dissatisfaction With the Use Of Intelligence Tests Fomentioning
confidence: 99%
“…He wrote a critical review of the literature on the effects of damage to the frontal lobes (Hebb, 1945) and continued to work on the measurement of adult intelligence (Hebb and Morton, 1944). He also developed new tests to measure verbal and non-verbal aspects of intelligence (Hebb and Morton, 1943). …”
Section: What Happened After 1941?mentioning
confidence: 99%
See 1 more Smart Citation
“…So, along with professor N.W. Morton of the McGill Psychology Department, Hebb began to develop two new tests: the verbal Adult Comprehension Test and the non-verbal Picture Anomaly Test (Hebb & Morton 1943). Second, Hebb observed that lesions of different brain areas produced different cognitive impairments.…”
Section: Neuropsychology At the Montreal Neurological Institute: 1937-39mentioning
confidence: 99%
“…Hebb and Morton (30,31) Halstead (24) investigated eighty tests in relation to senescence of which twenty-five were selected as a tentative battery. He showed that senile adults find difficulty in reversing old habit sequences, in retention of meaningful auditory and visual stimuli, in judgment, in planning, and in spatial discrimination, while they are better in rote memory and fluency of old associations.…”
Section: Tests Of Adult Intelligencementioning
confidence: 99%